2011
DOI: 10.1007/s12010-011-9235-x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Production of Triterpenoids of Ganoderma lucidum by an Ether Extract from the Medicinal Insect, Catharsius molossus, and Identification of the Key Stimulating Active Components

Abstract: The medicinal fungus Ganoderma lucidum was inoculated into the media with and without supplementation of medicinal insect extracts to screen stimulators from Chinese medicinal insects for mycelial growth and triterpenoids production in submerged fermentation. The methanol and ether extracts of the tested insects had no significant stimulatory effect on the mycelial biomass production (P > 0.05), and those of H. remigator and Mylabris phalerata markedly inhibited the mycelial growth. However, the ether extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 29 publications
(30 reference statements)
2
28
0
Order By: Relevance
“…To accelerate the production of metabolites by I. obliquus, effect of different lignocellulosic materials have been studied (18,21). Other studies also reported that the extracts from host-related species can stimulate mycelial biomass and metabolite production of medicinal mushroom such as Ganoderma lucidum (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…To accelerate the production of metabolites by I. obliquus, effect of different lignocellulosic materials have been studied (18,21). Other studies also reported that the extracts from host-related species can stimulate mycelial biomass and metabolite production of medicinal mushroom such as Ganoderma lucidum (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that the EECM concentration during fermentation was the key factor in triterpene production . In addition, a pH gradient or differing pH values for the first half and the second half of fermentation showed a significant effect on triterpene production .…”
Section: Methodsmentioning
confidence: 95%
“…The insect, C. molossus, was purchased from Bozhou Three Flavor Pharmaceutical Co. (Bozhou, Anhui, China). The EECM was prepared according to methods described in our previous work . EECM constituents are mainly fatty acids and fatty acid derivatives, of which, the putative active compounds, cis ‐9,10‐methylenehexadecanoic acid and hexadecanoic acid, represent 2.36% and 20.59% of the EECM constituents, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cha Ganoderma lucidum has long been used in the form of tea or powder to promote health and prolong life in China, Korea, and Japan (21). It is particularly known to contain pharmacologically active triterpenoids as well as a large amount of β-glucan, which is a type of polysaccharide, and it is effective in lowering blood pressure and reducing blood sugar levels, in addition to its antitumor and antioxidative activities (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%